Contribution of Anisotropic Electron Current to the Magnetotail Current Sheet as a Function of Location and Plasma Conditions. Issue 1 (7th January 2020) - Artemyev, A. V.; Angelopoulos, V.; Vasko, I. Y.; Petrukovich, A. A.; Runov, A.; Saito, Y.; Avanov, L. A.; Giles, B. L.; Russell, C. T.; Strangeway, R. J.
Abstract: The magnetotail current sheet carries the current responsible for the largest fraction of the energy storage in the magnetotail, the magnetic energy in the lobes. It is thus inextricably linked with the dynamics and evolution of many magnetospheric phenomena, such as substorms. The magnetotail current sheet structure and stability depend mostly on the kinetic properties of the plasma populating the magnetotail. One of the most underinvestigated properties of this plasma is electron temperature anisotropy, which may contribute a large fraction of the total current. Using observations from five missions in the magnetotail, we examine the electron temperature anisotropy, T e ‖ / T e ⊥, and its potential contribution to the current density, quantified by the firehose parameter ( β e ‖ − β e ⊥ )/2, across y ∈[−20, 20] R E and x ∈[−100, −10] R E . We find that a significant fraction (>30%) of all current sheets have an anisotropic electron current density >10% of the total current. These current sheets form two distinct groups: (1) near‐Earth (<30  R E ) accompanied by weak plasma flows (<100 km/s) and enhanced equatorial magnetic field (>3 nT) and (2) middle tail (>40  R E ) accompanied by fast plasma flows (>300 km/s) and small equatorial magnetic field (≤1 nT). For a significant number of near‐Earth current sheets, the anisotropic electron current can be >25% of the total current density. Our findings suggest that electron temperature anisotropy should be included in current sheet models describing realistic magnetotail structure and dynamics. Key Points: Parallel electron anisotropy is statistically observed in the magnetotail by five spacecraft missions In 10–20% of magnetotail current sheets the anisotropic electron current contributes more than 25% of the total current density Electron anisotropy is mostly evident in quiet current sheets with an enhanced equatorial magnetic field